Gang membership, drug sales, violence, and guns - Gonzalez Dominquez, Jose Fabian (2008)
The purpose of this study is to examine three factors relating to drug arrests using secondary data analysis. First, ethnic characteristics of a dealer were analyzed according to the location from where they sold their product. Next, possible factors associated with a police officer using force at the time of a drug arrest were also analyzed. Finally, factors associated with a gun being present at the time of a drug arrest were also analyzed